Cyclic Behavior Soft Clay Soil in Bangladesh - Ripon Hore, Ph.D.; Mehedi A. Ansary, Ph.D. (Academia One Publishing, 2023)
This paper represents the analysis of shaking table tests on wrap faced embankment lying on soft clay. The model embankment in a laminar box mounted on a shaking table, machine. The output results from the shaking table test are verified by numerical analysis. The different surcharge load with different acceleration has been varied in different model tests. It is observed from these tests that the response of the embankment with soft clay has been significantly affected by the base acceleration levels, and magnitude of surcharge pressure. In this research the data of Loma Prieta earthquake (1989) has been used in this experiment. The effects of these different parameters on acceleration response at different elevations of the embankment, and face deformations have also been presented. The result find that the proposed wrap faced embankment is great resist the earthquake especially like Loma Prieta and give an indicative performance measure of the wrap faced embankment on soft clay soil.
Keywords: Earthquake; Soft clay; embankment